﻿A new species of Astronotus (Teleostei, Cichlidae) from the Orinoco River and Gulf of Paria basins, northern South America - Alfredo Perez Lozano; Oscar M. Lasso-Alcalá; Pedro S. Bittencourt; Donald C. Taphorn; Nayibe Perez; Izeni Pires Farias (ZooKeys, 2022)
Based on morphological and molecular analysis of Astronotus species, a new species is described from the Orinoco River and Gulf of Paria basins in Venezuela and Colombia. Morphologically, it differs from Astronotus crassipinnis and Astronotus ocellatus in pre-orbital depth, caudal peduncle depth, head width, and caudal peduncle length, with significant differences in average percentage values. Osteologically, it differs from the two described species by lacking a hypurapophysis on the parahypural bone (hypural complex) and having two or three supraneural bones. Another characteristic that helps diagnose the new species is the morphology of the sagitta otolith, which is oval with crenulated dorsal and ventral margins and a rounded posterior edge. Genetically, the new species is distinct from all the other lineages previously proposed for the genus, delimited by five single locus species delimitation methods, and also has unique diagnostic nucleotides. Phylogenetic analyses support the monophyly of the new species as well as all other species/lineages. Astronotus species have considerable genetic, anatomical, and sagitta otolith shape differences, but have few significant traditional morphometric and meristic differences, because there is high variability in counts of spines, soft dorsal-fin rays, and lateral-line scales. It is clear that this new species is genetically and anatomically differentiated from all other species within the genus, and deserves recognition as a new valid species.